Innate Immune Activation and Circulating Inflammatory Markers in Preschool Children - Collier, Fiona; Chau, Cerys; Mansell, Toby; Faye-Chauhan, Keshav; Vuillermin, Peter; Ponsonby, Anne-Louise; Saffery, Richard; Tang, Mimi L. K.; O’Hely, Martin; Carlin, John; Gray, Lawrence E. K.; Bekkering, Siroon; et al. (Frontiers in Immunology, 2022)
The early life relationship between innate immune responses and inflammation may inform prevention of immune-related non-communicable diseases (NCDs). In adults, non-genetic host factors such as age, sex, and obesity, strongly impact cytokine production and circulating mediators, but data in preschool children are lacking. Here, we assessed cytokine responses and inflammatory markers in a population of healthy preschool children (mean age 4.2 years). Associations between cytokines, plasma inflammatory markers and sex, age, adiposity, season, and immune cell composition were investigated. Boys had higher IL-12p70 and IL-10 following TLR-stimulation. Adiposity and winter season were associated with increased inflammatory markers but not cytokine production. The inflammatory markers GlycA and hsCRP were associated with cytokine production and may therefore reflect innate immune function and inflammatory potential. This dataset will be informative for future prospective studies relating immune parameters to preclinical childhood NCD phenotypes.